Jana Pawła II prośba o przebaczenie i jej recepcja w prasie światowej [John Paul II’s request for forgiveness and its reception in the international press] - Szczepaniak, Maciej (Biuletyn Edukacji Medialnej [Media Education Bulletin], 2012)
From the perspective of the past years the pontificate of beatified John Paul II demands some deepened theological reflection over the events which significantly affected the Church’s image in the contemporary world. It seems that the pope’s request for forgiveness for sins committed by the faithful of the Church is one of the gestures which changed the course of history. This event received a lot of attention in the international press. This paper analyzes press articles published in American, French and Italian daily papers. The request for forgiveness was not only presented as a historical event but also as the pope’s reaction to real, contrary to taught principles and sinful deeds of the Church’s faithful, about which some of churchmen would rather remain silent. However, even the twisted view of presenting that event could transmit the evangelical truth, awaking in a recipient spiritual experience. That’s why “the day of forgiveness” may be called a pearl of John Paul II’s pontificate, who was able to make the topic of forgiveness one of the interpretive keys to his apostolic ministry.
https://katalog.adlr.link/Record/ai-53-24594